Impact of Wave–Current Interactions on the Detachment of Low-Salinity Water From Changjiang River Plume and Its Subsequent Evolution - Jiang, Zhipeng; Song, Dehai; Wei, Qinsheng; Ding, Yang (Frontiers in Marine Science, 2022)
The evolution of low-salinity water (LSW) detached from river plumes is critical to coastal systems and inner-shelf biogeochemical processes. In this study, the impact of wave–current interactions on the LSW detachment from the Changjiang River plume and its subsequent evolution is explored. Waves can advance the detachment of LSW through enhancing the vertical mixing, the northward intrusion of the inshore branch of the Taiwan Warm Current, and the upwelling. The wave-enhanced vertical mixing increases the core salinity of the initially isolated LSW and the growth rate of the core salinity during its subsequent evolution. Waves can lengthen the journey of the isolated LSW and accelerate its movement. Five wave–current interaction processes are compared and it is found that the wave-induced form drag contributes the most to the LSW detachment and its subsequent evolution. It enhances the vertical mixing and alters the wave-driven flow through the vertical transfer of wave-generated pressure to the momentum equation and the turbulent kinetic energy (TKE) equations. The wave dissipation working in the TKE equations weakens the northeastward flow off the Changjiang River estuary, which restrains the diluted water expansion. The current advection and refraction of wave energy contribute most to the enhancement of the double-core upwelling system.